Documentary : a history of the non-fiction film - Barnouw, Erik, 1908- (New York : Oxford University Press, 1993)
Surveys the history of documentary films and filmmaking from 1895 to the end of the twentieth century, and examines the development of technology over the decades along with the effects of video cassettes and cable television on the production of documentaries.
Includes bibliographical references (p. [361]-375) and index.
Adult
Keywords: Documentary films -- History and criticism; Documentary films -- History and criticism